The Effect of Ozone Gas on Dentin Shear Bond Strength - Yasemin Yavuz; Omer Cellik; Emrullah Bahsi; Bayram Ince (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Aim: The aim of this study was to investigate the effect of ozone used as cavity disinfectant on dentin bond strength of resin-based restorative material. Material and Method: The study included 36 adult 3rd molar teeth removed for surgical reasons. Each tooth was set in a cylindrical mould 2cm in diameter and 3cm high with the dentin surface parallel to the occlusal level and the roots remaining inside, with the help of autopolymerising acrylic. To obtain a standard smear layer, the teeth were filed. The teeth were randomly separated into 4 groups of 9. Ozone gas was applied to the dentin surfaces for 6 seconds (Prozone W&H, Bürmoos, Austria); Group 1 (single Bond Universal, Z250), Group 2 (ozone + single Bond Universal, Z250), Group 3 (Futurabond M, Grandio) Group 4 (Ozone + Futurabond M, Grandio). A 2mm resin layer was applied and polymerised with an LED light source for 20 secs (Light Emitting Diode-Elipar Freelight, 3M ESPE, Germany). The samples were applied with shear force of 1mm/min to breaking point. Results: No statistically significant difference was determined between the shear bond strength values of all the groups (p>0.05). No statistically significant difference was determined between the shear bond strength values in the paired comparison of the groups (p>0.05). Adhesive type fractures were determined in the majority of all the groups. Conclusion: The results of this study showed that ozone used for the purpose of disinfection had no negative effect on dentin shear bond strength.